Development of methods for spawning, fertilization, larval husbandry, and settlement in the temperate coral Astrangia poculata - E. M. Borbee; I. Changsut; J. S. McAlister; T. Demarco; S. W. Davies; C. F. Ianniello; M. Sánchez García; L. M. Roberson; A. Schickle; J. M. Sneed; G. Pelose; D. Wuitchik; et al. (Frontiers in Marine Science, 2026)
The temperate coral Astrangia poculata has recently emerged as a useful experimental organism for studying symbiosis, organism-environment interactions, and embryonic development. Crucial to the success of establishing any species as a laboratory animal are reliable husbandry protocols and the ability to culture the full life cycle in captivity. Here, we detail efforts resulting from several years (2016-2025) of collaboration by a multi-institutional group of researchers toward standardized and reproducible methods for A. poculata spawning, fertilization, larval husbandry, and settlement in the laboratory. Spawning in A. poculata can be reliably induced in the laboratory via thermal treatment, and the methods presented here yielded laboratory fertilization rates of up to 93%. Unfed larvae exhibit rates of development comparable to previous reports, and larvae supplemented with commercially available organic matter sources, including Reef Roids and Reef Snow, exhibited signs of accelerated development. Settlement (attachment and metamorphosis) of A. poculata larvae was achieved using tetrabromopyrrole (TBP), a small molecule previously shown to induce settlement and/or metamorphosis in several tropical coral species. The methods described here, including augmentation of A. poculata larval culture with feed, and TBP-triggered settlement, represent a necessary first step for culturing A. poculata individuals throughout the life cycle, which can be scaled and adapted to enable new lines of inquiry dependent on experimental manipulation of specific genetic host lineages, and/or early life stages.

Soil Microbial Diversity and Network Organization Respond to Land Use and Agricultural Inputs Worldwide - Zaki Saati‐Santamaría; Sergio Pérez‐Gorjón; Daniel Abel‐Schaad; Alberto Acedo‐Bécares; Francisca Alba‐Sánchez; Amanda Lucia Alves; Weronika Babinska‐Wensierska; Jorge Ariel Marfetán; Carolina Barroetaveña; Kara Barry; Francisco Beitia; Katerina Biniari; et al. (Global Change Biology, 2026)
Soil microbiomes are critical for ecosystem functioning, yet the global influences of climate and agricultural practices on their diversity and structure remain incompletely characterized. Here we analyzed 1921 soil samples from 33 countries worldwide across diverse biomes to assess how climate gradients and agricultural inputs, including pesticides and fertilizers, shape prokaryotic and fungal communities. We found that microbial diversity peaks at intermediate temperatures and differs markedly between natural and agricultural soils, with agriculture increasing microbial diversity while altering community composition and ecological guilds. Pesticide use selectively reduced bacterial diversity and shifted fungal guilds, decreasing ectomycorrhizal fungi while increasing saprotrophs, whereas fertilization reduced microbial network cohesion, with organic and inorganic fertilizers eliciting distinct community responses. These findings reveal that climatic factors and agricultural management jointly influence soil microbial diversity, community structure, and network connectivity, with implications for soil health and ecosystem resilience in managed landscapes. Overall, our results demonstrate that agricultural practices, including the use of pesticides and both organic and inorganic fertilizers, act as strong ecological filters that reshape soil microbiomes worldwide—enhancing apparent diversity but driving a functional shift toward less mutualistic, more fragmented, and potentially less resilient communities.

Environmental identities of college students reveal potential conflicts and common ground for wildlife conservation - Richard Von Furstenberg; Lincoln R. Larson; M. Nils Peterson; Kangjae Jerry Lee; Victoria R. Vayer; kathryn stevenson; Stacy A.C. Nelson; Jeremy Bruskotter; Adam A. Ahlers; Christine Anhalt-Depies; Taniya Bethke; Chris Chizinski; et al. (Biological Conservation, 2025)

Corrigendum: Restoration of herbivory on Caribbean coral reefs: are fishes, urchins, or crabs the solution? - Mark J. Butler; Alain Duran; Colette J. Feehan; Alastair R. Harborne; Alwin Hylkema; Joshua T. Patterson; William C. Sharp; Angelo Jason Spadaro; Tom Wijers; Stacey M. Williams (Frontiers in Marine Science, 2025)

Downregulation of Fidgetin-Like 2 Increases Microglial Function: The Relationship Between Microtubules, Morphology, and Activity - Austin N. Smith; Alison Gregor; Lisa Baker; David J. Sharp; Kimberly R. Byrnes (Molecular Neurobiology, 2025)
The microtubule cytoskeleton regulates microglial morphology, motility, and effector functions. The microtubule-severing enzyme, fidgetin-like 2 (FL2), negatively regulates cell motility and nerve regeneration, making it a promising therapeutic target for central nervous system injury. Microglia perform important functions in response to inflammation and injury, but how FL2 affects microglia is unclear. In this study, we investigated the role of FL2 in microglial morphology and injury responses in vitro. We first determined that the pro-inflammatory stimulus, lipopolysaccharide (LPS), induced a dose- and time-dependent reduction in FL2 expression associated with reduced microglial ramification. We then administered nanoparticle-encapuslated FL2 siRNA to knockdown FL2 and assess microglial functions compared to negative control siRNA and vehicle controls. Time-lapse live-cell microscopy showed that FL2 knockdown increased the velocity of microglial motility. After incubation with fluorescently labeled IgG-opsonized beads, FL2 knockdown increased phagocytosis. Microglia were exposed to low-dose LPS after nanoparticle treatment to model injury-induced cytokine secretion. FL2 knockdown enhanced LPS-induced cytokine secretion of IL-1α, IL-1β, and TNFα. These results identify FL2 as a regulator of microglial morphology and suggest that FL2 can be targeted to increase or accelerate microglial injury responses. Graphical Abstract

Review of APSIM's soil nitrogen modelling capability for agricultural systems analyses - Kirsten Verburg; Heather R. Pasley; Jody S. Biggs; Iris Vogeler; Enli Wang; Henrike Mielenz; Val O. Snow; Chris J. Smith; Chiara Pasut; Andrea D. Basche; Di He; Sotirios V. Archontoulis; et al. (Agricultural Systems, 2025)

SNAPSHOT USA 2019–2023: The First Five Years of Data From a Coordinated Camera Trap Survey of the United States - Brigit Rooney; Roland Kays; Michael V. Cove; Alex Jensen; Benjamin R. Goldstein; Christopher Pate; Paula Castiblanco; Maggie E. Abell; Jessie Adley; Briana Agenbroad; Adam A. Ahlers; Peter D. Alexander; et al. (Global Ecology and Biogeography, 2025)
Motivation SNAPSHOT USA is an annual, multicontributor camera trap survey of mammals across the United States. The growing SNAPSHOT USA dataset is intended for tracking the spatial and temporal responses of mammal populations to changes in land use, land cover and climate. These data will be useful for exploring the drivers of spatial and temporal changes in relative abundance and distribution, as well as the impacts of species interactions on daily activity patterns. Main Types of Variables Contained SNAPSHOT USA 2019–2023 contains 987,979 records of camera trap image sequence data and 9694 records of camera trap deployment metadata. Spatial Location and Grain Data were collected across the United States of America in all 50 states, 12 ecoregions and many ecosystems. Time Period and Grain Data were collected between 1st August and 29th December each year from 2019 to 2023. Major Taxa and Level of Measurement The dataset includes a wide range of taxa but is primarily focused on medium to large mammals. Software Format SNAPSHOT USA 2019–2023 comprises two .csv files. The original data can be found within the SNAPSHOT USA Initiative in the Wildlife Insights platform.

Random and systematic uncertainty in ship‐based seawater carbonate chemistry observations - Brendan R. Carter; Jonathan D. Sharp; Maribel I. García‐Ibáñez; Ryan J. Woosley; Michael B. Fong; Marta Álvarez; Leticia Barbero; Simon L. Clegg; Regina Easley; Andrea J. Fassbender; Xinyu Li; Katelyn M. Schockman; et al. (Limnology and Oceanography, 2024)
Seawater carbonate chemistry observations are increasingly necessary to study a broad array of oceanographic challenges such as ocean acidification, carbon inventory tracking, and assessment of marine carbon dioxide removal strategies. The uncertainty in a seawater carbonate chemistry observation comes from unknown random variations and systematic offsets. Here, we estimate the magnitudes of these random and systematic components of uncertainty for the discrete open‐ocean carbonate chemistry measurements in the Global Ocean Data Analysis Project 2022 update (GLODAPv2.2022). We use both an uncertainty propagation approach and a carbonate chemistry measurement “inter‐consistency” approach that quantifies the disagreement between measured carbonate chemistry variables and calculations of the same variables from other carbonate chemistry measurements. Our inter‐consistency analysis reveals that the seawater carbonate chemistry measurement community has collected and released data with a random uncertainty that averages about 1.7 times the uncertainty estimated by propagating the desired “climate‐quality” random uncertainties. However, we obtain differing random uncertainty estimates for subsets of the available data, with some subsets seemingly meeting the climate‐quality criteria. We find that seawater pH measurements on the total scale do not meet the climate‐quality criteria, though the inter‐consistency of these measurements improves (by 38%) when limited to the subset of measurements made using purified indicator dyes. We show that GLODAPv2 adjustments improve inter‐consistency for some subsets of the measurements while worsening it for others. Finally, we provide general guidance for quantifying the random uncertainty that applies for common combinations of measured and calculated values.

Discovery of imbricated beachrock deposits adjacent to the Java trench, Indonesia: influence of tsunami and storm waves, and implications for mega-thrust earthquakes - R. Harris; W. Meservy; H. Sulaeman; M. Bunds; J. Andreini; B. Sharp; B. Berrett; J. Whitehead; G. Carver; G. Setiadi; S. Hapsoro; C. Prasetyadi (Natural Hazards, 2024)

Restoration of herbivory on Caribbean coral reefs: are fishes, urchins, or crabs the solution? - Mark J. Butler; Alain Duran; Colette J. Feehan; Alastair R. Harborne; Alwin Hylkema; Joshua T. Patterson; William C. Sharp; Angelo Jason Spadaro; Tom Wijers; Stacey M. Williams (Frontiers in Marine Science, 2024)
That coral reefs are in decline worldwide, particularly in the Caribbean, will come as no surprise. This decades-long decline has reached a potential tipping point as the weight of the effects of climate change have come decidedly to bear on the planet’s most diverse marine ecosystem. Whether coral reefs can persist without restorative intervention is debatable, which has prompted a surge in coral reef restoration projects focusing primarily on the cultivation and transplantation of coral fragments onto degraded reefs. But that widespread approach does little to address the underlying causes of coral loss, one of which is the proliferation of macroalgae that are deleterious to corals. An emerging solution to this problem is the enhancement of herbivory on coral reefs through improved management of herbivores, artificial enhancement of herbivore settlement, or their mariculture and subsequent stocking. This review explores the nuances of the biology of well-studied Caribbean coral reef herbivores (fishes, sea urchins, and crabs) as it relates to their mariculture and investigates the promise of herbivore stocking onto coral reefs as a restoration strategy. Fish, urchin, and crab herbivores differ appreciably in life histories, which confers advantages and disadvantages with respect to their mariculture and effectiveness as grazers. Mariculture of herbivorous marine fish for reef restoration is essentially non-existent so the reestablishment of grazing fish abundance on coral reefs focuses primarily on their protection through fishery regulations, but only at a few locations in the Caribbean. Mariculture of herbivorous urchins and crabs for restoration purposes is in its infancy, but promising especially for crabs whose larval rearing is less difficult. Perhaps the biggest challenge for the mariculture of either taxon is “scaling-up” from research settings to large-scale mariculture needed for stocking. Numerous studies extol the benefits of functional redundancy and complementarity for coral reef ecosystem stability, but whether this principal applies to the restoration of grazing function is untested. We identify gaps in our knowledge of best practices for the restoration of grazing function on coral reefs and conclude with some practical guidance on the establishment of targets for macroalgal reduction, along with strategic advice on grazer stocking in a given reef habitat.

Uncertainty sources for measurable ocean carbonate chemistry variables - Brendan R. Carter; Jonathan D. Sharp; Andrew G. Dickson; Marta Álvarez; Michael B. Fong; Maribel I. García‐Ibáñez; Ryan J. Woosley; Yuichiro Takeshita; Leticia Barbero; Robert H. Byrne; Wei‐Jun Cai; Melissa Chierici; et al. (Limnology and Oceanography, 2024)
The ocean carbonate system is critical to monitor because it plays a major role in regulating Earth's climate and marine ecosystems. It is monitored using a variety of measurements, and it is commonly understood that all components of seawater carbonate chemistry can be calculated when at least two carbonate system variables are measured. However, several recent studies have highlighted systematic discrepancies between calculated and directly measured carbonate chemistry variables and these discrepancies have large implications for efforts to measure and quantify the changing ocean carbon cycle. Given this, the Ocean Carbonate System Intercomparison Forum (OCSIF) was formed as a working group through the Ocean Carbon and Biogeochemistry program to coordinate and recommend research to quantify and/or reduce uncertainties and disagreements in measurable seawater carbonate system measurements and calculations, identify unknown or overlooked sources of these uncertainties, and provide recommendations for making progress on community efforts despite these uncertainties. With this paper we aim to (1) summarize recent progress toward quantifying and reducing carbonate system uncertainties; (2) advocate for research to further reduce and better quantify carbonate system measurement uncertainties; (3) present a small amount of new data, metadata, and analysis related to uncertainties in carbonate system measurements; and (4) restate and explain the rationales behind several OCSIF recommendations. We focus on open ocean carbonate chemistry, and caution that the considerations we discuss become further complicated in coastal, estuarine, and sedimentary environments.

The distribution, ecology and predicted habitat use of the Critically Endangered angelshark ( Squatina squatina ) in coastal waters of Wales and the central Irish Sea - Joanna Barker; Jake Davies; Monika Goralczyk; Surshti Patel; John O'Connor; Jim Evans; Rowland Sharp; Matthew Gollock; Fenella R. Wood; James Rosindell; Charlie Bartlett; Brett J. Garner; et al. (Journal of Fish Biology, 2022)
The angelshark ( Squatina squatina ) has the northernmost range of any angel shark species, but there is limited information on its distribution, habitat use and ecology at higher latitudes. To address this, Angel Shark Project: Wales gathered 2231 S. squatina records and 142 anecdotal resources from fishers, coastal communities and archives. These spanned the coastal waters of Wales and the central Irish Sea and were dated from 1812 to 2020, with 97.62% of records within 11.1 km (6 nm) of the coast. Commercial, recreational and charter boat fishers provided the majority of S. squatina records (97.18%), with significantly more sightings from three decades (1970s, 1980s and 1990s) and in the months of September, June, August and July (in descending order). The coastal area between Bardsey Island and Strumble Head had the most S. squatina records ( n = 1279), with notable concentrations also found in Carmarthen Bay, Conwy Bay and the Outer Severn Estuary. Species distribution models (SDM) identified four environmental variables that had significant influence on S. squatina distribution, depth, chlorophyll‐a concentration, sea surface temperature (SST) and salinity, and these varied between the quarters (Q) of the year. SDM model outputs predicted a larger congruous area of suitable habitat in Q3 (3176 km 2 ) compared to Q2 (2051 km 2 ), with suitability along the three glacial moraines (Sarn Badrig, Sarn‐y‐Bwch and Sarn Cynfelyn) strongly presented. Comparison of modelled environmental variables at the location of S. squatina records for each Q identified reductions in depth and salinity, and increases in chlorophyll‐a and SST when comparing Q2 or Q3 with Q1 or Q4. This shift may suggest S. squatina are making seasonal movements to shallow coastal waters in Q2 and Q3. This is supported by 23 anecdotal resources and may be driven by reproductive behaviour, as there were 85 records of S. squatina individuals ≤60 cm in the dataset, inferred as recently born or juvenile life‐history stages. The results have helped fill significant evidence gaps identified in the Wales Angelshark Action Plan and immediate next research steps are suggested.

Prediction of disability-free survival in healthy older people - Johannes Tobias Neumann; Le T. P. Thao; Anne M. Murray; Emily Callander; Prudence R. Carr; Mark R. Nelson; Rory Wolfe; Robyn L. Woods; Christopher M. Reid; Raj C. Shah; Anne B. Newman; Jeff D. Williamson; et al. (GeroScience, 2022)
Prolonging survival in good health is a fundamental societal goal. However, the leading determinants of disability-free survival in healthy older people have not been well established. Data from ASPREE, a bi-national placebo-controlled trial of aspirin with 4.7 years median follow-up, was analysed. At enrolment, participants were healthy and without prior cardiovascular events, dementia or persistent physical disability. Disability-free survival outcome was defined as absence of dementia, persistent disability or death. Selection of potential predictors from amongst 25 biomedical, psychosocial and lifestyle variables including recognized geriatric risk factors, utilizing a machine-learning approach. Separate models were developed for men and women. The selected predictors were evaluated in a multivariable Cox proportional hazards model and validated internally by bootstrapping. We included 19,114 Australian and US participants aged ≥65 years (median 74 years, IQR 71.6–77.7). Common predictors of a worse prognosis in both sexes included higher age, lower Modified Mini-Mental State Examination score, lower gait speed, lower grip strength and abnormal (low or elevated) body mass index. Additional risk factors for men included current smoking, and abnormal eGFR. In women, diabetes and depression were additional predictors. The biased-corrected areas under the receiver operating characteristic curves for the final prognostic models at 5 years were 0.72 for men and 0.75 for women. Final models showed good calibration between the observed and predicted risks. We developed a prediction model in which age, cognitive function and gait speed were the strongest predictors of disability-free survival in healthy older people. Trial registration Clinicaltrials.gov (NCT01038583)

Best Practice Data Standards for Discrete Chemical Oceanographic Observations - Li-Qing Jiang; Denis Pierrot; Rik Wanninkhof; Richard A. Feely; Bronte Tilbrook; Simone Alin; Leticia Barbero; Robert H. Byrne; Brendan R. Carter; Andrew G. Dickson; Jean-Pierre Gattuso; Dana Greeley; et al. (Frontiers in Marine Science, 2022)
Effective data management plays a key role in oceanographic research as cruise-based data, collected from different laboratories and expeditions, are commonly compiled to investigate regional to global oceanographic processes. Here we describe new and updated best practice data standards for discrete chemical oceanographic observations, specifically those dealing with column header abbreviations, quality control flags, missing value indicators, and standardized calculation of certain properties. These data standards have been developed with the goals of improving the current practices of the scientific community and promoting their international usage. These guidelines are intended to standardize data files for data sharing and submission into permanent archives. They will facilitate future quality control and synthesis efforts and lead to better data interpretation. In turn, this will promote research in ocean biogeochemistry, such as studies of carbon cycling and ocean acidification, on regional to global scales. These best practice standards are not mandatory. Agencies, institutes, universities, or research vessels can continue using different data standards if it is important for them to maintain historical consistency. However, it is hoped that they will be adopted as widely as possible to facilitate consistency and to achieve the goals stated above.

Correction to: Histamine, mast cell tryptase and post-exercise hypotension in healthy and collapsed marathon runners - I. T. Parsons; M. J. Stacey; L. Faconti; N. Hill; J. O’Hara; E. Walter; B. Farukh; R. McNally; H. Sharp; A. Patten; R. Grimaldi; N. Gall; et al. (European Journal of Applied Physiology, 2021)

Histamine, mast cell tryptase and post-exercise hypotension in healthy and collapsed marathon runners - I. T. Parsons; M. J. Stacey; L. Faconti; N. Hill; J. O’Hara; E. Walter; B. Farukh; R. McNally; H. Sharp; A. Patten; R. Grimaldi; N. Gall; et al. (European Journal of Applied Physiology, 2021)
Purpose Heat stress exacerbates post-exercise hypotension (PEH) and cardiovascular disturbances from elevated body temperature may contribute to exertion-related incapacity. Mast cell degranulation and muscle mass are possible modifiers, though these hypotheses lack practical evidence. This study had three aims: (1) to characterise pre–post-responses in histamine and mast cell tryptase (MCT), (2) to investigate relationships between whole body muscle mass (WBMM) and changes in blood pressure post-marathon, (3) to identify any differences in incapacitated runners. Methods 24 recreational runners were recruited and successfully completed the 2019 Brighton Marathon (COMPLETION). WBMM was measured at baseline. A further eight participants were recruited from incapacitated runners (COLLAPSE). Histamine, MCT, blood pressure, heart rate, body temperature and echocardiographic measures were taken before and after exercise (COMPLETION) and upon incapacitation (COLLAPSE). Results In completion, MCT increased by nearly 50% from baseline ( p = 0.0049), whereas histamine and body temperature did not vary ( p > 0.946). Systolic (SBP), diastolic (DBP) and mean (MAP) arterial blood pressures and systemic vascular resistance (SVR) declined ( p < 0.019). WBMM negatively correlated with $$Δ $$ Δ SBP ( r = − 0.43, p = 0.046). For collapse versus completion, there were significant elevations in MCT (1.77 ± 0.25 μg/L vs 1.18 ± 0.43 μg/L, p = 0.001) and body temperature (39.8 ± 1.3 °C vs 36.2 ± 0.8 °C, p < 0.0001) with a non-significant rise in histamine (9.6 ± 17.9 μg/L vs 13.7 ± 33.9 μg/L, p = 0.107) and significantly lower MAP, DBP and SVR ( p < 0.033). Conclusion These data support the hypothesis that mast cell degranulation is a vasodilatory mechanism underlying PEH and exercise associated collapse. The magnitude of PEH is inversely proportional to the muscle mass and enhanced by concomitant body heating.

Opposing Indirect Effects of Domestic Herbivores on Saltmarsh Erosion - Jordi F. Pagès; Stuart R. Jenkins; Tjeerd J. Bouma; Elwyn Sharps; Martin W. Skov (Ecosystems, 2019)

Phosphodiesterase 4 inhibition affects both the direct and indirect pathway: an electrophysiological study examining the tri-phasic response in the substantia nigra pars reticulata - P. R. A. Heckman; J. V. Schweimer; T. Sharp; J. Prickaerts; A. Blokland (Brain Structure and Function, 2018)

Biomarkers of Acute Stroke Etiology (BASE) Study Methodology - Edward C. Jauch; Andrew D. Barreto; Joseph P. Broderick; Doug M. Char; Brett L. Cucchiara; Thomas G. Devlin; Alison J. Haddock; William J. Hicks; Brian C. Hiestand; Glen C. Jickling; Jeff June; David S. Liebeskind; et al. (Translational Stroke Research, 2017)

Functional neuroimaging of visuo-vestibular interaction - R. E. Roberts; H. Ahmad; Q. Arshad; M. Patel; D. Dima; R. Leech; B. M. Seemungal; D. J. Sharp; A. M. Bronstein (Brain Structure and Function, 2017)

Effects of the potential lithium-mimetic, ebselen, on impulsivity and emotional processing - Charles Masaki; Ann L. Sharpley; Charlotte M. Cooper; Beata R. Godlewska; Nisha Singh; Sridhar R. Vasudevan; Catherine J. Harmer; Grant C. Churchill; Trevor Sharp; Robert D. Rogers; Philip J. Cowen (Psychopharmacology, 2016)

Understanding Climate Adaptation on Public Lands in the Upper Midwest: Implications for Monitoring and Tracking Progress - Christine M. Anhalt-Depies; Tricia Gorby Knoot; Adena R. Rissman; Anthony K. Sharp; Karl J. Martin (Environmental Management, 2016)

The geology of the carbonate-hosted Blende Ag–Pb–Zn deposit, Wernecke Mountains, Yukon, Canada - Micheal Moroskat; Sarah A. Gleeson; R. J. Sharp; A. Simonetti; C. J. Gallagher (Mineralium Deposita, 2015)

Assessing the sensitivity of habitats to fishing: from seabed maps to sensitivity maps a - N. C. Eno; C. L. J. Frid; K. Hall; K. Ramsay; R. A. M. Sharp; D. P. Brazier; S. Hearn; K. M. Dernie; K. A. Robinson; O. A. L. Paramor; L. A. Robinson (Journal of Fish Biology, 2013)
In the Welsh part of the Irish Sea, a method was developed for assessing the sensitivity of different seabed habitats to existing fishing activities, across a range of potential fishing intensities. The resistance of 31 habitats and their associated biological assemblage to damage by 14 categories of fishing activity were assessed along with the rate at which each habitat would recover following impact (resilience). Sensitivity was scored based on a combination of the resistance of a habitat to damage and its subsequent rate of recovery. The assessments were based, wherever possible, on scientific literature, with expert judgement used to extrapolate results to habitat and gear combinations not directly examined in the published literature. The resulting sensitivity matrices were then subject to further peer review at a series of workshops. Following consensus on the habitat sensitivity, these data were combined with the most resolved sea‐floor habitat maps. These habitat sensitivity maps can help inform the development of site‐specific management plans, as well as having a place in spatial planning and aiding managers in developing dialogue with other stakeholders. A case study of their application is provided.

Maximizing information from space data resources: a case for expanding integration across research disciplines - Nandu Goswami; Jerry J. Batzel; Gilles Clément; T. Peter Stein; Alan R. Hargens; M. Keith Sharp; Andrew P. Blaber; Peter G. Roma; Helmut G. Hinghofer-Szalkay (European Journal of Applied Physiology, 2013)

A simple temperature-based model predicts the upper latitudinal limit of the temperate coral Astrangia poculata - J. L. Dimond; A. H. Kerwin; R. Rotjan; K. Sharp; F. J. Stewart; D. J. Thornhill (Coral Reefs, 2013)

Variability and change in the Canadian cryosphere - C. Derksen; S. L. Smith; M. Sharp; L. Brown; S. Howell; L. Copland; D. R. Mueller; Y. Gauthier; C. G. Fletcher; A. Tivy; M. Bernier; J. Bourgeois; et al. (Climatic Change, 2012)
During the International Polar Year (IPY), comprehensive observational research programs were undertaken to increase our understanding of the Canadian polar cryosphere response to a changing climate. Cryospheric components considered were snow, permafrost, sea ice, freshwater ice, glaciers and ice shelves. Enhancement of conventional observing systems and retrieval algorithms for satellite measurements facilitated development of a snapshot of current cryospheric conditions, providing a baseline against which future change can be assessed. Key findings include: 1. surface air temperatures across the Canadian Arctic exhibit a warming trend in all seasons over the past 40 years. A consistent pan-cryospheric response to these warming temperatures is evident through the analysis of multi-decadal datasets; 2. in recent years (including the IPY period) a higher rate of change was observed compared to previous decades including warming permafrost, reduction in snow cover extent and duration, reduction in summer sea ice extent, increased mass loss from glaciers, and thinning and break-up of the remaining Canadian ice shelves. These changes illustrate both a reduction in the spatial extent and mass of the cryosphere and an increase in the temporal persistence of melt related parameters. The observed changes in the cryosphere have important implications for human activity including the close ties of northerners to the land, access to northern regions for natural resource development, and the integrity of northern infrastructure.

Functional convergence of microbes associated with temperate marine sponges - M. Ribes; E. Jiménez; G. Yahel; P. López‐Sendino; B. Diez; R. Massana; J. H. Sharp; R. Coma (Environmental Microbiology, 2012)
Summary Most marine sponges establish a persistent association with a wide array of phylogenetically and physiologically diverse microbes. To date, the role of these symbiotic microbial communities in the metabolism and nutrient cycles of the sponge‐microbe consortium remains largely unknown. We identified and quantified the microbial communities associated with three common Mediterranean sponge species, Dysidea avara , Agelas oroides and Chondrosia reniformis ( Demospongiae ) that cohabitate coralligenous community. For each sponge we quantified the uptake and release of dissolved organic carbon (DOC) and nitrogen (DON), inorganic nitrogen and phosphate. Low microbial abundance and no evidence for DOC uptake or nitrification were found for D. avara . In contrast A. oroides and C. reniformis showed high microbial abundance (30% and 70% of their tissue occupied by microbes respectively) and both species exhibited high nitrification and high DOC and NH 4 + uptake. Surprisingly, these unique metabolic pathways were mediated in each sponge species by a different, and host specific, microbial community. The functional convergence of microbial consortia found in these two sympatric sponge species, suggest that these metabolic processes may be of special relevance to the success of the holobiont.

The Changing Arctic Cryosphere and Likely Consequences: An Overview - M. S. Olsen; T. V. Callaghan; J. D. Reist; L. O. Reiersen; D. Dahl-Jensen; M. A. Granskog; B. Goodison; G. K. Hovelsrud; M. Johansson; R. Kallenborn; J. Key; A. Klepikov; et al. (Ambio, 2011)

Are Underlying Assumptions of Current Animal Models of Human Stroke Correct: from STAIRs to High Hurdles? - Renée J. Turner; Glen C. Jickling; Frank R. Sharp (Translational Stroke Research, 2011)

Gender-Dependent Correlations of Carotid Intima–Media Thickness with Gene Expression in Blood - Renée J. Turner; Cheryl D. Bushnell; Thomas C. Register; Frank R. Sharp (Translational Stroke Research, 2011)

Combined resistance and endurance training improves physical capacity and performance on tactical occupational tasks - Nathan R. Hendrickson; Marilyn A. Sharp; Joseph A. Alemany; Leila A. Walker; Everett A. Harman; Barry A. Spiering; Disa L. Hatfield; Linda M. Yamamoto; Carl M. Maresh; William J. Kraemer; Bradley C. Nindl (European Journal of Applied Physiology, 2010)

The Environmental Polymorphisms Registry: a DNA resource to study genetic susceptibility loci - Patricia C. Chulada; Heather L. Vahdat; Richard R. Sharp; Tracy C. DeLozier; Paul B. Watkins; Susan N. Pusek; Perry J. Blackshear (Human Genetics, 2008)

Simultaneous blockade of 5-HT1A/B receptors and 5-HT transporters results in acute increases in extracellular 5-HT in both rats and guinea pigs: in vivo characterization of the novel 5-HT1A/B receptor antagonist/5-HT transport inhibitor SB-649915-B - Zoë A. Hughes; Kathryn R. Starr; Claire M. Scott; Michael J. Newson; Trevor Sharp; Jeannette M. Watson; Jim J. Hagan; Lee A. Dawson (Psychopharmacology, 2007)

Development and genetic mapping of sequence-tagged microsatellites (STMs) in bread wheat (Triticum aestivum L.) - M. J. Hayden; P. Stephenson; A. M. Logojan; D. Khatkar; C. Rogers; J. Elsden; R. M. D. Koebner; J. W. Snape; P. J. Sharp (Theoretical and Applied Genetics, 2006)

Aromatase inhibition abolishes courtship behaviours in the ring dove (Streptopelia risoria) and reduces androgen and progesterone receptors in the hypothalamus and anterior pituitary gland - M. D. C. Belle; P. J. Sharp; R. W. Lea (Molecular and Cellular Biochemistry, 2005)

Molecular structure of a novel y-type HMW glutenin subunit gene present in Triticum tauschii - M. E. Hassani; M. C. Gianibelli; M. R. Shariflou; P. J. Sharp (Euphytica, 2005)

Isotopic ( 13 C and 14 C) evidence supporting the transformative effect of cattle on north Australian vegetation - D. M. J. S. Bowman; B. R. Sharp; U. Zoppi (Journal of Biogeography, 2004)

A new approach to extending the wheat marker pool by anchored PCR amplification of compound SSRs - M. J. Hayden; P. Stephenson; A. M. Logojan; D. Khatkar; C. Rogers; R. M. D. Koebner; J. W. Snape; P. J. Sharp (Theoretical and Applied Genetics, 2004)

The irreversible cattle‐driven transformation of a seasonally flooded Australian savanna - Ben R. Sharp; Robert J. Whittaker (Journal of Biogeography, 2003)
Aim Anecdotal historical and photographic evidence suggests that woody vegetation is increasing dramatically in some northern Australian savanna habitats. Vegetation change in savannas has important implications for pastoral land‐use, conservation management, and landscape‐scale carbon storage, and informs theoretical debates about ecosystem function. This study seeks to determine the nature, extent and cause(s) of woody vegetation change in a seasonally flooded alluvial savanna habitat. Location The study area is located within the seasonally inundated alluvial zone of the tidal portion of the Victoria River, Northern Territory, Australia. The study area has been grazed by domestic stock since c. 1900, prior to which the area was inhabited and more likely regularly burnt by Aboriginal people for thousands of years. Methods Digital georeferenced aerial photographic coverages were used to examine and quantify woody vegetation change between 1948 and 1993. Transect surveys of woody and herbaceous vegetation were carried out to ground‐truth air‐photo results and determine the nature and causes of observed vegetation changes. Results There has been a dramatic increase in woody vegetation cover throughout the study area. Vegetation change patterns are roughly uniform across the full range of edaphic habitat variation and are unrelated to the depositional age of fluvial sediments. Two woody species, Eucalyptus microtheca and Excoecaria parvifolia , are predominantly responsible for observed increases. Demographic analyses reveal that woody invasions have been episodic and indicate that in most locations peak woody species establishment occurred in the mid‐1970s. Grasses are almost absent in a majority of habitats within the study area. Instead, large areas are covered by scalded soil, dense invasive weed populations, and unpalatable forbs and sedges. What grasses do occur are predominantly of very low value for grazing. The condition of the herbaceous layer renders most of the study area almost completely non‐flammable; what fires do burn are small and of low intensity. Main conclusions Multiple working hypotheses explaining observed patterns of woody vegetation increase were considered and rejected in turn. The only hypothesis consistent with the evidence is as follows: (1) observed changes are a direct consequence of extreme overgrazing by cattle, most likely when stocking rates peaked in the mid‐1970s; (2) prolonged heavy grazing effected the complete transformation of much of the herbaceous vegetation to a new state that is not flammable; and (3) in the absence of regular fire mortality, woody vegetation increased rapidly. The relatively treeless system that existed in 1948 was apparently stable and resilient to moderate grazing levels, and perhaps also to episodic heavy grazing events. However, grazing intensity in excess of a sustainable threshold has forced a transition that is irreversible in the foreseeable future. Stable‐state transitions such as this one inform debates at the heart of ecological theory, such as the nature of stability, resilience, equilibrium and carrying capacity in dynamic savanna ecosystems.

Genetic mapping of 66 new microsatellite (SSR) loci in bread wheat - P. Gupta; H. Balyan; K. Edwards; P. Isaac; V. Korzun; M. Röder; M.–F. Gautier; P. Joudrier; A. Schlatter; J. Dubcovsky; R. De la Pena; M. Khairallah; et al. (Theoretical and Applied Genetics, 2002)

Characterisation of Triticum vavilovii-derived stripe rust resistance using genetic, cytogenetic and molecular analyses and its marker-assisted selection - H. S. Bariana; G. N. Brown; N. U. Ahmed; S. Khatkar; R. L. Conner; C. R. Wellings; S. Haley; P. J. Sharp; A. Laroche (Theoretical and Applied Genetics, 2002)

Poster Session - J. van S. Graver; H. J. Banks; A. K. Sharp; A. Contessi; N. Baldassari; M. Maggioli; Sabine Prozell; Ch. Reichmuth; Maria Otília Carvalho; Ana Paula Pereira; A. Mexia; Sylvia Allen; et al. (Phytoparasitica, 2001)

Comparison of microbial populations in model and natural rumens using 16S ribosomal RNA‐targeted probes - Cherie J. Ziemer; Richard Sharp; Marshall D. Stern; Michael A. Cotta; Terence R. Whitehead; David A. Stahl (Environmental Microbiology, 2000)
A model rumen system, dual‐flow continuous culture fermenters, was evaluated by two comparative criteria in two experiments using ribosomal (r)RNA‐targeted DNA probes to compare key microbial groups in samples. The initial experiment measured temporal changes in population structure during adaptation of ruminal microbial populations in fermenters over 240 h. The fermenter inoculum contained 34.9% Bacteria, 60.1% Eukarya and 6.8% Archaea measured as a fraction of total small subunit (SSU) rRNA quantified using a universal probe. The cellulolytic bacterial genus Fibrobacter comprised 9.5% of total SSU rRNA in the inoculum. After 240 h of fermenter operation, the average abundance was 80.9% Bacteria, 6.1% Eukarya, 5.1% Archaea and Fibrobacter genus accounted for 6.6% of the total SSU rRNA. Divergence between ruminal and fermenter population structure was evaluated in the second experiment and samples were classified as ruminal, inoculum or fermenter (96, 120, 144 and 168 h of fermenter operation). Fermenter samples had higher relative abundances of Bacteria (84.5%) and Archaea (2.1%) and lower relative abundances of Eukarya (1.8%) than ruminal samples (average 48.0% Bacteria, 1.3% Archaea and 61.5% Eukarya). The relative abundance of Fibrobacter was similar in all samples, averaging 2.5%. The ruminal and fermenter samples had similar proportions of F. succinogenes and F. succinogenes subgroup 3 (as a percentage of Fibrobacter SSU rRNA). Fibrobacter succinogenes subgroup 1 and F. intestinalis proportions of Fibrobacter were lower in fermenter samples (8.2% and 0.7% respectively) than in ruminal samples (28.4% and 2.2% respectively). Fermenters were able to maintain a core prokaryotic community structure similar to the native microbial community in the rumen. Although protozoa populations were lost, maintenance of Fibrobacter and archaeal populations indicated that the model system supported a functional community structure similar to the rumen. This model rumen system may serve as a suitable tool for studying aspects of ruminal microbial ecology and may resolve some of the relationships between microbial community structure and function by providing control of experimental conditions.

A microbiological survey of Montserrat Island hydrothermal biotopes - Tony Atkinson; Steven Cairns; D. A. Cowan; Michael J. Danson; David W. Hough; D. Barrie Johnson; Paul R. Norris; Neil Raven; Clare Robinson; Rob Robson; Richard J. Sharp (Extremophiles, 2000)

Xp deletions associated with autism in three females - N. S. Thomas; Andrew J. Sharp; Caroline E. Browne; David Skuse; Chris Hardie; Nicholas R. Dennis (Human Genetics, 1999)

Does erythrocyte infusion improve 3.2-km run performance at high altitude? - Kent B. Pandolf; Andrew J. Young; Michael N. Sawka; James L. Kenney; Mark W. Sharp; Randy R. Cote; Beau J. Freund; C. Robert Valeri (European Journal of Applied Physiology, 1998)

A study of females with deletions of the short arm of the X chromosome - Rowena S. James; Brian Coppin; Paola Dalton; Nicholas R. Dennis; Caroline Mitchell; Andrew J. Sharp; David H. Skuse; N. Simon Thomas; P. A. Jacobs (Human Genetics, 1998)

The effect of infusion of hypertonic saline on glomerular filtration rate and arginine vasotocin, prolactin and aldosterone in the domestic chicken - A. M. Leary; J. R. Roberts; P. J. Sharp (Journal of Comparative Physiology B, 1998)

A novel method for regenerating the protoplasts of thermophilic bacilli - R. M. Dunn; M. J. Munster; R. J. Sharp; B. N. Dancer (Archives of Microbiology, 1987)